Predicting the distribution of Eastern Grey Kangaroos by remote sensing assessment of food resources. - Rollings, Nick M.; Moss, Graeme L. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
This study demonstrates how the distribution of animals can be described usingremotely sensed data at a scale in the order of square kilometers. Kangaroo distributionhas been monitored at regional scales using aerial surveys and detailed field study. Thisstudy attempts to fill the gap between local and regional scales by using Landsat derivedvegetation characteristics to provide animal distribution details at local scale. Field surveysof Eastern Grey kangaroos and vegetation biomass were undertaken at the WarrumbungleNational Park, New South Wales, Australia. The distribution and abundance of kangaroosand plant biomass were compared with remotely sensed vegetation characteristics takenfrom Landsat TM imagery. The distribution of green, short (< 5cm) blade grass biomass(the preferred kangaroo food resource) was patchy and positively correlated with kangaroodensity and Landsat spectral bands 1, 2, 3 and a principal component combination of bands1-7 (excluding band 6). Total population density was positively correlated with bladegrass biomass and Landsat band 3. The dispersion of kangaroos within habitats waspatchy, even though the Landsat image defined habitats as being homogeneous. This studyclearly demonstrates the value of Landsat data to environmental management in the pastand present.